Compendium of Transport Statistics Government of India - Planning Commission (Planning Commission, 1994)
This is the second issue of "Compendium of Transport Statistics". We have taken the opportunity to enlarge, revise and update the data brought out in the previous issue. The work has involved extensive collation of data on different modes of transport and systematic classification thereof. Plan-wise time series data is a distinctive feature of this publication. It is hoped this document will be found useful by all agencies concerned with transport planning.
Government of India, Planning Commission, (Transport Division)
Government of India Planning Commission